Evaluation of reported cases of drug poisoning between 2017 and 2022 in the State of Paraná (Research, Society and Development, 2025)
This study aims to analyze cases of drug poisoning in the state of Paraná, using data from the Notifiable Diseases Information System (SINAN) in the period from 2017 to 2022. Socioeconomic data were collected, such as toxic agent, age group, education, race, sex, circumstances and evolution of cases. The results showed that the drugs were responsible for 59% of the notifications of exogenous intoxication, followed by drugs of abuse and products for home use. As for the age group, young adults (20 to 39 years) had the highest proportion of cases, followed by adolescents (15 to 19 years). Most cases occurred in people with complete high school, white and female. The suicide attempt was identified as the circumstance with the highest percentage of notifications and admittedly a serious public health problem and a significant challenge to be faced. These results highlight the importance of drugs as intoxicating agents and highlight the need for preventive and educational measures for the proper use of these substances. In addition, the predominance of cases in young adults suggests the need for specific prevention and intervention strategies for this group, with emphasis on promoting self-care and education about the appropriate use of substances. The research provides relevant information that can assist in the formulation of public policies to improve pharmaceutical care and promote the rational use of medicines.